On The ‘Dia-Techné Dialogue Through Art’ Methodology - Carrascosa, Alex (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
This essay presents the ‘Dia-Techné · Dialogue through Art’ methodology, a tool for group or community facilitation created autonomously from the field of plastic and visual arts in response to different needs arising in the field of Peace Education suchas transitional justice processes (research on truth and symbolic reparation), memory, positive conflict transformation, direct democracy and councilism, community regeneration, intercultural dialogues and non-violent resistance.